Severe Polyhydramnios with Consistent Fetal Full Bladder: A Novel Sign of Antenatal Bartter's Disease - Thakur, Seema; Kumar, Manisha; Malhotra, Supriya; Paliwal, Preeti; Thareja, Vandana; Sahi, Gaurika (Journal of Pediatric Genetics, 2020)
Bartter's disease, an inherited renal tubular disorder is due to a defect in ion transport across the ascending limb of the loop of Henle leading to failure of the ability of kidneys to concentrate urine and hence polyuria. We present three fetuses of mothers with severe polyhydramnios with normal maternal blood sugar profile, routine Toxoplasma, Rubella, Cytomegalovirus, Herpes (TORCH) serology. The ultrasound showed no structural anomaly in the fetus, but consistent overdistended bladder with severe polyhydramnios was observed without any evidence of obstructive uropathy. The biochemical test on amniotic fluid was suggestive of Bartter's disease in case 1 and borderline in case 2, and next-generation sequencing confirmed a mutation of KCNJ1 associated with Bartter's disease Type II in case 1 and a mutation in SLC21A1 in case 2. Amniotic fluid biochemistry was inconclusive in case 3. A consistent full bladder with severe polyhydramnios with onset around 24 to 25 weeks was a novel finding which was observed due to fetal polyuria and can be used as a clue to investigate cases with severe polyhydramnios with no structural anomaly. Antenatal diagnosis will help in the proper management of child and genetic counseling for the next pregnancy.
Keywords: polyhydramnios; overdistended bladder; Bartter's disease; SLC21A1; KCNJ1